Atraumatic fracture of nonmodular femoral stem - Pintore, Andrea; Toro, Giuseppe; Di Napoli, Giuseppe; Vecchio, Gianluca; Gargano, Giuseppe; Calabrò, Giampiero (Lo Scalpello - Journal, 2024)
Introduction. Femoral stem fracture is a rare cause of revision total hip replacement. Nonmodular extensively porous coated stems, well-fixed and non-cemented, have significant bone adhesion. Case report. A 56-year-old patient presented to the emergency room with a proximal fracture of a nonmodular stem in the portion of the neck, in absence of trauma or fall. The femoral stem was well fixed without any signs of osteolysis, with the result that the extraction instrumentation was ineffective to remove it. A transfemoral Wagner osteotomy was deemed necessary for removal of the femoral stem, and implantation of a Wagner revision stem. At 3 months of follow-up the patient walked without the aid of crutches and X-rays showed a correct integration of the implant. Conclusions. No cases of atraumatic fracture of the proximal region of the nonmodular stem not associated with risk factors have been described in the literature. With a perfect integration of the proximal and distal prosthetic implant, a transfemoral osteotomy is necessary.